2021
DOI: 10.1111/cdev.13690
|View full text |Cite
|
Sign up to set email alerts
|

Toward complementarity: Specificity and commonality in social‐emotional development

Abstract: What are the roles of specificity and commonality in social-emotional development?We begin by highlighting the conceptual context for this timely and timeless question and explain how responses to it can inform novel lines of theoretical and empirical inquiry, as well as sociocultural generalizability. Next, we describe how the selection of papers included in this special section contributes to our understanding of specificity and commonality in social-emotional development. We then explain how applying the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 56 publications
7
24
0
Order By: Relevance
“…Furthermore, in line with previous studies (Downey & Condron, 2004), we found that the high number of children in low-educated families is disadvantageous for children's language skills (in the UK and in the US) only. Thus, our findings align with the complementarity principle in child development, which suggests that different outcomes might simultaneously be affected by common and specific factors (Malti & Cheah, 2021). Disparities in family structure and in language spoken at home were only related to language and social skills in the UK and in the US, respectively, which might result from country-specific differences in these factors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, in line with previous studies (Downey & Condron, 2004), we found that the high number of children in low-educated families is disadvantageous for children's language skills (in the UK and in the US) only. Thus, our findings align with the complementarity principle in child development, which suggests that different outcomes might simultaneously be affected by common and specific factors (Malti & Cheah, 2021). Disparities in family structure and in language spoken at home were only related to language and social skills in the UK and in the US, respectively, which might result from country-specific differences in these factors.…”
Section: Discussionsupporting
confidence: 84%
“…In particular, our results point out -in line with the assumptions of FIMs which particularly focus on the importance of parental investments for child development -the importance of HLE for gaps in both language and social skills. In fact, it proved to be the only factor accounting for gaps across the different developmental domains and countries, which aligns with the commonality principle (Malti & Cheah, 2021). From the HLE variables, especially the more frequent reading to the child in families with high-educated parents turned out to account for SES-related differences in children's language and social skills.…”
Section: Discussionsupporting
confidence: 53%
“…These results also speak to the importance of considering strengths-based associations in refugee youth [17,32], and align with past studies involving typically developing lower-risk samples or samples exposed to different risk contexts, such as children from low-income homes [74]. Importantly, our results extend the findings of these studies to the refugee context, which adds to existing literature by further suggesting that emotion regulation and sympathy may serve as common themes in mental health (particularly, externalizing symptoms) across populations [75]. The capacity to flexibly regulate emotions may support refugee children's coping with the challenges and resulting stress of their unique experiences, thereby promoting their internalizing and externalizing symptoms upon resettlement.…”
Section: Main Effects Of Child Social-emotional Capacities On Child Internalizing and Externalizing Symptomssupporting
confidence: 86%
“…Notably, our bivariate correlation results revealed that higher trust was associated with lower emotion regulation, further suggesting that the capacity for interpersonal trust may work differently among children who have experienced severe interpersonal adversities. While the current results support the specificity principle (i.e., the notion that outcomes will vary depending on the specificities of the group under study) [75], they also align with select past work indicating the limitations of "too much trust" or "too little trust" in typically developing samples. Specifically, some studies have documented a curvilinear association between trust and mental health in children and adolescents, with higher and lower levels of trust being associated with poorer mental health (indexed by both internalizing symptoms and aggression) relative to moderate levels of trust [79,80].…”
Section: Main Effects Of Child Social-emotional Capacities On Child Internalizing and Externalizing Symptomssupporting
confidence: 74%
See 1 more Smart Citation